1990
DOI: 10.1016/0378-1097(90)90689-n
|View full text |Cite
|
Sign up to set email alerts
|

A radical-chemical route to acetyl-CoA: the anaerobically induced pyruvate formate-lyase system of Escherichia coli

Abstract: Anaerobically growing Escherichia coli cells contain the enzyme pyruvate formate‐lyase which catalyses the non‐oxidative cleavage of pyruvate to acetyl‐CaA and formate. The enzyme is subject to interconversion between inactive and active forms. The active form contains an oxygen‐sensitive organic free radical located on the polypeptide chain which is essential for catalysis. It affords a novel homolytic C‐C bond cleavage of the pyruvate substrate. The radical is generated by an iron‐dependent converter enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(147 citation statements)
references
References 49 publications
3
144
0
Order By: Relevance
“…Although this behavior did exist in the unregulated modeled population as a relatively small set of cells at intermediate to fast growth rates, the number of cells predicted to engage in this behavior is significantly expanded under regulation due to the lack of alternate avenues for NADH oxidation. Interestingly, both PFL and LDH use are known to be associated with anaerobic growth (28,29). The microarray data used in imposing regulatory constraints indicates that PFL is downregulated a modest 2.6-fold-well below our cutoff for strong down-regulation-despite an average measured copy number in excess of 200 per cell.…”
Section: Growth Rates and Flux Distributionsmentioning
confidence: 99%
“…Although this behavior did exist in the unregulated modeled population as a relatively small set of cells at intermediate to fast growth rates, the number of cells predicted to engage in this behavior is significantly expanded under regulation due to the lack of alternate avenues for NADH oxidation. Interestingly, both PFL and LDH use are known to be associated with anaerobic growth (28,29). The microarray data used in imposing regulatory constraints indicates that PFL is downregulated a modest 2.6-fold-well below our cutoff for strong down-regulation-despite an average measured copy number in excess of 200 per cell.…”
Section: Growth Rates and Flux Distributionsmentioning
confidence: 99%
“…Such flickering was found in other ion channels, including the inward-rectifying potassium channel Kir2.1 (23) and also the ClC chloride channels (24,25). The "fast gate" could be a single, flexible amino acid side chain in the transport channel, as is the case with the "Glu ex " glutamate residue in ClC channels (25,26). Its strict conservation within the FNT family makes H209 in the center of the channel a likely candidate (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Western blot analysis of the levels of pyruvate formate-lyase (PflB), which generates formate from the cleavage of pyruvate (Knappe & Sawers, 1990), revealed that PflB levels (Fig. 3a, bottom panel) correlated with the presence of the Hyd-3 large subunit (Fig.…”
Section: Manno(fructo)kinase Is Not the Main Route Of Fructose Entry mentioning
confidence: 99%
“…3a). The double band in the Western blot of PflB is indicative of the presence of active, radicalcontaining enzyme in the cell at the time of cell breakage (Knappe & Sawers, 1990). …”
Section: Manno(fructo)kinase Is Not the Main Route Of Fructose Entry mentioning
confidence: 99%